PENTINGNYA IMAN DAN TAQWA DALAM KEHIDUPAN MANUSIA - Syiintia Purnama; Karnila Br Tarigan; Edi Hermanto (Cahaya Ilmu Bangsa Institute, 2024)
Faith and piety are two fundamental concepts in human life that play an important role in shaping individual character and behavior. Faith refers to a deep belief in God and His teachings, which is not only cognitive but also emotional and spiritual. Faith provides purpose and meaning in life and serves as a source of motivation when facing various challenges. Piety reflects awareness and obedience to God's commands, as well as efforts to avoid His prohibitions. These two concepts provide clear guidance for living a meaningful life. The two complement each other, with faith as the basis of belief and piety as the manifestation of this belief in daily actions. This study aims to explore the role of faith and piety in human life, including their impact on ethics, social relationships, and individual well-being. The methodology used includes a literature review based on faith and piety. The conclusion of this study emphasizes the importance of integrating faith and piety into everyday life to achieve spiritual and social well-being. Recommendations are given to improve education and understanding of these values in society as a step toward building a more harmonious and ethical community.